Formulation and Physical Evaluation of Antihypertensive Sustained-Release Tablet From Matoa Leaf Ethanolic Extract (Pometia pinnata J.R & G.Forst) - Arifuddin Yunus; Siti Qurrataayun; Lutfiah Lutfiah (Sanata Dharma University, 2026)
Matoa leaf extract (Pometia pinnata J.R & G.Forst), known for its antihypertensive compound quercetin-3-O-rhamnoside, was developed into sustained-release tablets to improve its bioavailability. This study used the direct compression method with xanthan gum as the polymer matrix. The resulting tablets were then rigorously evaluated. A series of physical tests were conducted, including organoleptic assessment, uniformity of weight and size, hardness, friability, and moisture content. The biopharmaceutical properties were analyzed through in-vitro disintegration and dissolution tests using UV-Vis spectrophotometry. The findings demonstrated that formulation F3 was the most optimal. It successfully passed all physical stability standards, confirming its excellent mechanical properties. In the dissolution test, F3 achieved the highest absorbance value of 0.29, indicating a consistent and controlled release of the active ingredient. This optimal release was sustained over 6 to 10 hours, with an active substance content of 12%. Therefore, the F3 formulation is confirmed as a successful and effective sustained-release tablet, offering a promising approach for drug delivery.